2017
DOI: 10.1021/acsomega.7b00603
|View full text |Cite
|
Sign up to set email alerts
|

New Understanding on Photocatalytic Mechanism of Nitrogen-Doped Graphene Quantum Dots-Decorated BiVO4 Nanojunction Photocatalysts

Abstract: Bismuth vanadate (BiVO 4 ) is a promising candidate as a visible-light-driven photocatalyst in the aspect of practical applications. To investigate the origin of active species from BiVO 4 and understand the influence of the variations of the photocatalytic process, comparative studies on zero-dimensional nitrogen-doped graphene quantum dot (NGQD)-decorated BiVO 4 have been carried out for methylene blue photodegradation. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…light absorption edge was slightly blue shifted [21]. The UV-vis spectrum of NGQDs is shown in Figure S4d, and the band gap was approximately 1.56 eV, according to our previous work [30,41]. After decorating NGQDs, it was found that there was an increasing visible light absorption for all composites.…”
Section: Optical and Electrical Propertiessupporting
confidence: 66%
“…light absorption edge was slightly blue shifted [21]. The UV-vis spectrum of NGQDs is shown in Figure S4d, and the band gap was approximately 1.56 eV, according to our previous work [30,41]. After decorating NGQDs, it was found that there was an increasing visible light absorption for all composites.…”
Section: Optical and Electrical Propertiessupporting
confidence: 66%
“…Many attempts have been made to combat this through co-catalyst modifications to form heterojunctions or phase-junctions, doping with non-metals or metals such as Fe, W, N, P and Mo, and tuning morphology with the aim to expose most reactive facets 10 . Doping involves the introduction of impurity levels that act as electron or hole traps thus facilitation separation of electrons and holes 12,13 . Co-catalyst modifications to form heterojunctions or phase-junctions depends on the band-edge staggered alignment that facilitate the shuttle of electrons and holes to different materials by separating the respective charge transporters.…”
Section: Introductionmentioning
confidence: 99%
“…To further validate the role and generation of active species in the photocatalytic degradation of organic pollutants, it is important to understand the relative positions of the VB and CB potentials in the CTMG20 nanocomposite with respect to the reduction potentials of O 2 / * O 2 − (−0.33 eV), O 2 /H 2 O 2 (+0.69 eV), * OH/OH − (+1.99 eV) and * OH/H 2 O (+2.68 eV) . In this regard, the relative band edge positions of the photocatalyst were calculated by using the following equations [Eqs.…”
Section: Resultsmentioning
confidence: 99%